Broadband terahertz absorber based on multi-band continuous plasmon resonances in geometrically gradient dielectric-loaded graphene plasmon structure - Yang, Jiawen (Sci Rep, 2018)
We propose a broadband terahertz absorber consisting of nonstructured graphene loaded with arrays of elliptic dielectric cylinders. The relative bandwidth for the absorption above 90% reaches about 65%. The working mechanism of broad bandwidth mainly comes from two aspects. One is that the nonstructured graphene loaded with elliptic dielectric cylinders provides multiple discrete graphene plasmon resonances with large relative frequency interval. The other is that, for each discrete resonance, there exists a set of continuous plasmon resonances because the width of the dielectric structure varies continuously and gradiently. The broadband terahertz absorber we demonstrate here, based on geometrically gradient dielectric structures and nonstructured graphene, avoids the graphene processing, which shows great potential applications in related devices.